Tecer, lançar e recolher redes de saberes ambientais de atores sociais envolvidos com a suinocultura - Meller, Cleria Bittencorte (Universidade do Vale do Rio do Sinos, 2007)
The data from the report of the socioenvironmental diagnostic made by Profill Engenharia e Ambiente and by the following net of the conditions of the waters from Hydrographic Basin of Turvo, Santa Rosa and Santo Cristo Rivers by FEPAM, associated with the actions in the management from the Basin Committee, they indicate that the rivers from that basin can be contaminated by the dejections of pig farming, considered by the environmental inspection agency as one of the biggest problems from the modern farming. In face of this reality it was chosen to investigate the knowledge and the doings related to the environment dimension that were being built by the social actors from the Hydrographic Basin of Turvo, Santa Rosa and Santo Cristo Rivers, when in a environmental dimension of Education those are urged to take advantage of the dejections of their productions to minimize the impacts of them in the environment. For the data collecting were realized thematic workshops with students from High School; debating gro
Keywords: saberes ambientais; suinocultura; bacia hidrográfica; pig farming; environment knowledge; hydrographic basin; Ciências Humanas